The Effect of Training and Career Development on Job Satisfaction in the NCVS 1.16 Assembling Division at PT. Adis Dimension Footwear, Tangerang Regency - Hidayat, Dadan; Soebadio, Bizzma Buana Amriki (Faculty of Science and Technology University of Pramita Indonesia, 2026)
The purpose of this study was to determine how much influence training and career development simultaneously have on employee job satisfaction in the Assembling NCVS 1.16 section at PT. Adis Dimension Footwear Tangerang Regency.This study uses a quantitative descriptive method. The population in this study were all employees in the Assembling NCVS 1.16 section at PT Adis Dimension Footwear Tangerang Regency. The research sample consisted of 84 respondents.The results of this study indicate that (1) partially, training significantly influences employee job satisfaction in the Assembling NCVS 1.16 section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value> t table (5.505> 1.990) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, careerdevelopment significantly influences employee job satisfaction in the AssemblingNCVS 1.16 section at PT. Adis Dimension Footwear, Tangerang Regency, asindicatedby the calculated t value> t table (3.492> 1.990) and the significance value of 0.000is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, training and career development significantly influence employee job satisfaction in the Assembling NCVS 1.16 section at PT. Adis Dimension Footwear,Tangerang Regency, as indicated by Fcount> Ftable (56.385>3.11) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the training and career development variables, both partially and simultaneously, have a significant influence on employee job satisfaction in the Assembling NCVS 1.16 section at PT.Adis Dimension Footwear, Tangerang Regency.